Legal Analysis of Return Orders Not Delivered to Destination by Couriers from the Perspective of the Compilation of Sharia Economic Law (Case Study in Tanjung Pura District) - Nurhidayati, Nurhidayati; Hasanah, Uswatun (Law Development Journal, 2024)
In e-commerce transactions in the marketplace application, courier obligations must be ensured to be realized properly, the issue of returning goods (return) in the world of e-commerce is not uncommon. Researchers found a situation where the return occurred because the ordered goods were not delivered to the destination by the courier, and asked the buyer to pick up the order himself, the buyer who did not agree to cause the ordered goods to be returned back to the seller, so the research with the title "Legal Review of Return Orders Not Delivered to the Destination by Couriers from the Sharia Economic Law Compilation Perspective" with the object of couriers and users in Tanjung Pura District is important to analyze the law of the situation where the order is returned because the courier does not deliver the order to the agreed address, Researchers found the results in the Compilation of Sharia Economic Law Article 85 concerning Handover of Goods which explains that the place that has been determined to receive the goods is the place where the courier must deliver the ordered goods, if the courier breaks the promise, at the end of changing the place of receipt of the goods, the buyer has the right to cancel the contract, then in the Compilation of Sharia Economic Law in Article 36 concerning Mislead, in this case the party who does not fulfill his obligations can be subject to sanctions.